Exploring how Undergraduate BSc (Hons) Nursing (Child) Students Learn About End of Life Care Through Simulation – A Descriptive Case Study. - Ford, Lisa (International Journal of Practice-based Learning in Health and Social Care, 2023)
Research suggests that nursing students have many anxieties about dealing with death and dying and feel unprepared to care for these patients as newly registered nurses. Effective education has been found to be an important factor in preparing nursing students for end of life care. Simulation is a pedagogical strategy widely used within nursing education and can provide an opportunity for students to develop their end of life care skills in the absence of opportunities in the practice setting. The purpose of this study was to explore how BSc (Hons) Nursing (Child) students learn about end of life care through simulation. A new simulation pedagogy was designed and delivered to second year child nursing students, and case study methodology was used to explore student learning. Data was collected through a focus group discussion and individual interviews. The findings revealed that during simulation, students learned about end of life care through a combination of hands-on practice and reflection, collaborating with their peers and facilitators, and by engaging in the experience through the provision of a safe and authentic environment. Learning theory was applied to the findings in order to explain the simulation learning process. In conclusion, learning through simulation is socially constructed, occurring through experiential learning which promotes perspective transformation. Student engagement in the simulation learning process is influenced by effective and supportive facilitation.